The Role Of HRM Practices in Shaping Organisational Innovation in Malaysia Waqf Institutions: A Conceptual Paper - Farouk, Kaci; Embi, Nor Azizan Che; Hamid, Zabeda Abdul; Juhdi, Nurita (South Asian Journal of Social Sciences and Humanities, 2023)
The current pace of change in the world is unprecedented. As a result, the environment of NPO institutions and organisations has been affected by this rapid change, particularly the major development in the domains of management and the requirements of the society they serve. Third sector organisations, particularly waqf institutions, must constantly innovate in order to maintain a competitive advantage and achieve their goals of high economic and social values. Human resource management practices can be used to achieve this goal. Thus, the objective of this research is to examine the correlation between human resource management practices and organisational innovation. Using a cross-sectional approach, the study involved waqf institutions in Malaysia. Two human resource management practices served as independent variables in this study (performance appraisal and training and development). Organization innovation (Product / service innovation) was used as dependent variable.